The effectiveness of peer mentoring on school wellbeing in nursing students at Universitas Jenderal Achmad Yani Yogyakarta - Utami, Khristina Dias; Riyadi, Sujono; Sumiyarini, Retno (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: School well-being is an important aspect for students in determining their success during their studies and their future. Low school well-being will have an impact on the emergence of mental problems and academic problems in students. Peer mentoring is needed as a form of assistance, carried out by more experienced individuals (mentors) to help less experienced individuals (mentees).Objective: To find out how effective peer mentoring is for Unjaya Nursing students on school well-being.Methods: In quantitative form with a cross-sectional approach, the school well-being instrument was tested for validity and reliability first. The sample was 40 nursing students at Jenderal Achmad Yani University, Yogyakarta. Results: The average school well-being score before the intervention was 83.43 and after 83.85 peer mentoring was given, there was an increase in the score of 0.42. The school well-being score before and after the intervention was in the form of non-normally distributed data, and was tested using the Wilcoxon Signed Rank Test.with sig 0.638.Conclusion: The peer mentoring that is carried out is less effective in improving the school well-being of nursing students.